An Unusual Case of Acute-on-Chronic Liver Failure Leading to Liver Transplantation: Case Report - Brianna Coogle; Stephen Waller; Stephanie Wood; Joshua Smith; Ryan M. Taylor (Annals of Internal Medicine: Clinical Cases)
We report a case of acute-on-chronic liver failure manifesting as fulminant hepatitis caused by acute infection with hepatitis C virus in a patient with chronic cirrhosis secondary to former alcohol use. As a treatable cause with readily accessible testing, acute infection should be considered as a possible cause in all cases of acute-on-chronic liver failure. Hepatitis C virus viral load testing should be the test of choice to avoid missing a diagnosis in the window period of acute infection.